Program prizanesljivosti - novost v slovenski konkurenčnopravni ureditvi - Podobnik, Klemen (Pravni letopis, 2009)
The provision of Article 76 of the Prevention of Restriction of Competition Act is a novelty of the Slovenian competition regulation. The system of immunity from fines and the reduction of fines to parties of anti-competitiveagreements or concerted practices which have as their object or effect the prevention, restriction or distortion of competition, is primarily aimed to uncover and put an end to cartel business practices and their negative consequences. The article analyzes the Slovenian leniency programme which was modelled upon the Leniency Notice of the European Commission. The author detects certain factual and legal deficiencies which are yet to be abolished for the system to work effciently and attain its goals. In addition, comparative analysis of the leniency system in the United States, as well as some recent theoretical concepts are presented.
Keywords: konkurenca; konkurenčno pravo; kršenje; sankcije; varstvo konkurence